Contralateral Anterior Interhemispheric–Transcallosal–Transrostral Approach for the Resection of a Subcallosal Cavernous Malformation: A Case Report and an Operative Video - Costa Alves, Aderaldo; Zanini, Marco Antônio [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Chaddad-Neto, Feres Eduardo Aparecido (Frontiers, 2022)
This case report demonstrates the surgical resection of a cerebral cavernous malformation located in the subcallosal region. The authors present a detailed operative video explaining the steps to successfully remove the lesion through a contralateral interhemispheric–transcallosal–transrostral approach with the patient in lateral decubitus. The surgical procedure was uneventful, and the patient had no postoperative deficits and no residual lesions in a three-month follow-up.
Keywords: brain surgery; cerebral cavernous malformation (CCM); Interhemispheric approach; lateral decubitus position; microsurgery